Composting of biodegradable wastes from the university restaurant at Tecnológico de Costa Rica - Chaves-Arias, Raizeth (2019)
The university restaurant from Tecnológico de Costa Rica ́s main Campus in Cartago, has the purpose of a better waste management; therefore, three composting methods were evaluated to produce organic fertilizer from its biodegradable residues. The researchers selected the techniques through expert ́s opinion, assessing variables like pH, temperature, moisture and efficiency in each technique, in order to determine the most efficient one to re-valorize the organic waste. A factorial experimental design was selected, in which three treatments were compared: Takakura (TK), Mountain microorganisms (MM) and Pellets (P) with biodegradable solid wastes on each case, in tumbling composters and in pile composters (on the ground), with two repetitions. The used p value was 0,05. As a result, the Takakura treatment showed the best results from a technical, environmental and economic point of view, since it reached the highest average temperature (53°C) and achieved the thermophilic phase faster than the other ones, maintaining the expected indicators for proper composting, such as a pH close to 7, moisture between 50% and 70% and efficiency of 81%.. Consequently, the researchers conclude this treatment represents a valid strategy to aim towards a circular economy approach at the university ́s restaurant from Tecnológico de Costa Rica.